Pengembangan E-Modul Dengan Pendekatan SETS (Science, Environment, Technology, and Society) Pada Materi Lingkaran Siswa Kelas XI - Suradi, Suradi; Akram, Nurwahida; Rahman, Abdul (Issues in Mathematics Education (IMED), 2024)
This study is a Research and Development (R&D) aimed at developing an e-module with the SETS (Science, Environment, Technology, and Society) approach on Circle material for 11th-grade students at SMA Negeri 2 Majene. This development research is conducted to determine the validity, practicality, and effectiveness of the developed e-module with the SETS approach. The R&D study adopts the 4-D model (Four D Models) developed by Thiagarajan et al. (1974), which consists of four stages, namely: Define (Definition Stage), Design (Design Stage), Development (Development Stage), and Dissemination (Dissemination Stage). The validity results of the e-module with the SETS approach used assessment sheets by material experts and media experts. Based on the analysis, the scores from the material and media expert validators were out of an ideal score of , categorized as highly valid. For the practicality results of the e-module with the SETS approach, teacher and student response questionnaires were used. The analysis of the questionnaires showed that the teacher response score was (categorized as very practical) and the student response score was (categorized as very practical), thus the practicality of the e-module with the SETS approach is categorized as very practical. Lastly, the effectiveness of the e-module with the SETS approach was evaluated using learning outcome test questions. Based on the analysis of the learning outcome tests, out of students () met the Minimum Completeness Criteria (MCC), thus the effectiveness of the e-module is categorized as very effective.